Canada, aboriginal sealing, and the North Pacific Fur Seal Convention - Irwin, Robert (My University, 2015)
The National Oceanic and Atmospheric Administration has described the 1911 North Pacific Fur Seal Convention as one of the ten most important events in environmental history. Article IV of this Convention provided First Nation sealers with harvest rights provided they conducted the hunt as practiced previously, without the use of firearms and not under contract to a commercial interest. While historians have studied the diplomatic and environmental aspects of the Convention, little attention has been paid to this Aboriginal harvest privilege. Its inclusion in the fur seal treaty inadvertently contributes to the modern “ecological Indian” construction and foreshadows the current environmental crisis faced by many First Nation communities: their harvest is acceptable provided it is considered primitive or traditional and noncommercial.
Keywords: 1911 North Pacific Fur Seal Convention; environmental history; First Nation sealers; hunt; Aboriginal harvest privilege; fur seal treaty; environmental crisis; First Nation communities